EVALUATION OF PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY OF PITS AND FLESH OFDATE VAIRITIES - S. Khalid; 2A. Ahmad; 3T. Masud; 4M. J. Asad (Journal of Animal and Plant Sciences, 2021)
To analyze the nutraceutical potential of different varieties of dates and phytochemical extraction capabilities of different solvents, the present study was planned to determine antioxidant activity, polyphenolic contents ofpits and flesh of three date varieties (zaidy, aseel and ajwa) were determined in different solvents (Acetone, Methanol and Ethanol) and their respective three concentrations (70%, 80% and 90%). Correlation among all parameters for both parts were analyzed through Pearson correlation test. The results indicated pits as richest source for polyphenolic contents, DPPH and ABTS activity than flesh for all cultivars being highest in ajwa pits (3932.3 mg GAE/100g, 2956.2 mg QEC/100g, 96.3% and 86.2%respectively). In comparative analysis of solvents, 80% ethanol extracted highest antioxidant activity in all date parts. For polyphenols, different solvents have different effects on date parts so a single solvent cannot be recommended. Correlation analysis showed that phenolics have substantial positive correlation with flavonoids, DPPH and ABTS while flavonoids also revealed intensely positive relationship with DPPH and ABTS. DPPH and ABTS also exposed strongly increasing relation. In PCA analysis phenolics, flavonoids and antioxidant activity showed strong correlation in pits while showed weak relation in flesh parts. This study classifies erraticism between pits and flesh parts of date cultivars for their bioactive components which can be utilized as active ingredients against different maladies.
Keywords: Phenols; DPPH; Ajwa; PCA; Pits